Stereotipe Masyarakat Tentang Islamophobia Melalui Atribut Islam (Studi pada Masyarakat Napal Melintang Kecamatan Pino Raya Kabupaten Bengkulu Selatan) - Sri Narti; Vethy Octaviani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The emergence of stereotypes about Islamophobia had influenced by the development of the mass media, which can convey the message that Islam is a strict religion and is synonymous with terrorism simultaneously throughout the world. The existence of news with the labeling of symbols embedded in Muslims had attached as an image of terrorists. This study aims to investigate how Islamic signs in society construct Islamophobia. This study uses a qualitative research method with a phenomenological approach. Data collection techniques used were observation and in-depth interviews. The topics in this study were each three people from an urban and rural region in Bengkulu. The results show that the societal importance of Islamophobia had influenced by negative stereotypes regarding Islamic symbols. The forming process meaning develops in society itself based on direct experience, adaptation, and go by mass media. The created stereotypes lead to negative stigma, where both urban and rural communities experience Islamophobia and have negative perceptions when they see a community using Islamic symbols or attributes. However, some people have the opposite view that not all people or communities with Islamic signs are called terrorists or carriers of heretical teachings and are identical with violence because of the belief that Islam does not teach its people to commit violence against humans. So, it had concluded that Islamic symbols used by a community in certain activities could build a negative stereotype in most people about the Islamic religion that eventually creates Islamophobia in the community.